Obstacle Avoidance in Mobile Robotic Sensors and Establishing Connection. (2016) - Sebi, Sherin Ann; Sunny, Divya
Abstract: The Mobile Robotic Sensor Network (MRSN), require reliable applications and coordination based on strong network connectivity. These sensors are deployed into hazardous environment such as extreme temperature, mudslides, explosion etc. Chances of failure is high in sensor during operation which leads to easy compromise on connectivity due to interference. Based on the survey undertaken on DARA, LeDiR, they faces obstacle collision and sensor collision. The proposed method OCRS avoids the problem of obstacle avoidance and also introduces the concept of gyroscopic force. OCRS is implemented with the help of backup selection algorithm. On the basis of implementation done with the help of system model and control input it proves OCRS is more efficient than the existing system.